Sintesis, Karakterisasi Struktur, dan Kajian Molecular Docking Senyawa Turunan 4’-Metoksi Flavonol sebagai Antagonis Reseptor Estrogen Alpha (ER-a) pada Kanker Payudara - Ihsan Ikhtiarudin; Rahma Dona; Neni Frimayanti; Rahayu Utami; Nurul Susianti; Abdi Wira Septama (Jurnal Riset Kimia, 2022)
A long period of drug administration in breast cancer chemotherapy can cause various side effects. These situations encourage researchers to search for and develop alternative anticancer drugs through various approaches. This study aimed to synthesize a flavonol derivative (TF4) and to study the interactions of the synthesized compound with ER-α as one of the targeted receptors in breast cancer treatment. The synthesis was carried out using the stirring method and the study of interactions of TF4 with ER-α was performed through molecular docking against ER-α crystal structures bound to an antagonist (PDB ID: 3ERT) and agonist (PDB ID: 1A52). The synthesis of TF4 produced crude product in 58 % yield and pure product in 6 % yield. The structure of TF4 was confirmed by spectroscopic analyses including UV, FT-IR, 1D, and 2D NMR. The docking results showed that the TF4 does not form any conventional hydrogen bond with ER-α. However, it can form carbon-hydrogen (C--H) bonds and van der Walls interactions with several important residues on the active site of ER-α. In addition, the binding free energy values of TF4 (-9.14 and -9.50 kcal/mol) are more negative than estradiol (E2) as one of the natural ligands for ER-α. Thus, it can be estimated that TF4 can be bounded easier on the active site of ER-α than its natural ligand. It may presume that it can act as an estrogen antagonist because of the similarity in interactions and binding poses compared to TAM, TOR, dan 4-OHT as reference drug molecules.